GRID2 Mutation-Related Spinocerebellar Ataxia Type 18: A New Report and Literature Review - Panda, Prateek Kumar; Sharawat, Indar Kumar; Dawman, Lesa (Journal of Pediatric Genetics, 2020)
Spinocerebellar ataxias (SCAs) are heterogeneous disorders with multiple genetic etiology. Mutations in the GRID2 gene are associated with spinocerebellar ataxia type 18 (SCA-18). We report the first Indian case of SCA-18. The proband is a 7-year-old boy with motor delay, cerebellar signs, and cerebellar atrophy. Whole exome and direct sequencing identified compound heterozygous mutations of the coding and noncoding regions of the GRID2 gene. A literature review of the published cases with pathogenic GRID2 variants was performed. Beside our patients, 32 cases were identified. The majority of reported cases were males, of consanguineous kindreds, with autosomal recessive inheritance. However, a proportion of cases (39%) had autosomal dominant/semidominant inheritance with heterozygous variants. In addition to childhood-onset cerebellar ataxia, other reported features were: early-onset dementia, complicated spastic paraparesis, retinal dystrophy, hearing loss, lower motor neuron signs, and severe global developmental delay in some homozygous cases. Cerebellar atrophy was the commonest neuroimaging finding, with few cases demonstrating brain stem, supratentorial, and white matter abnormalities. Although SCA-18 should be suspected in patients with early-onset cerebellar ataxia, eye movement abnormalities, and motor delay, clinicians should be aware of late-onset, variable presentations with pyramidal signs, dementia, and hearing loss. In suspected cases, if mutations were not detected by whole-exome sequencing, direct sequencing of noncoding regions and chromosomal microarray should be considered.
Keywords: spinocerebellar ataxia; SCA-18; GRID2 gene; cerebellar atrophy; autosomal; semidominant inheritance